The hour of the 4th shared mobility mode: Mopeds. Why moped sharing will continue gaining global relevance. Status quo, trends and challenges. - Howe, Enrico (Trialog Publishers, 2021)
Since 2012, moped sharing has made a substantial and sustainable development within the shared mobility landscape. Last year the market hit the 100,000 moped threshold for the first time. This article gives you an intro to how moped sharing has developed in the past years, where it stands today (market status quo and existing challenges), and moreover where it is heading (trends). The article argues that moped sharing has a bright future ahead. Moped sharing has become a solid complementation of the three existing shared mobility modes bike, car and kick scooter.
Keywords: Verkehrsmittel; Verkehrsanteil; Verkehrsdienstleistung; Gemeinschaftsnutzung; Verkehrswende; Stadtverkehr; Moped; Kleinkraftrad; Shared Mobility